(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This thesis presents the best strategy to implement a conducive working environment and ensure a comfortable physical space for customers. We must also consider work performance in relation to the work environment since it is the most important element. This thesis also proposes a good factor about a conducive office working environment that can influence and produce high performance and good outcomes for efficient and effective work. We must remember that employees are more than the most important asset for any organization or company. The researchers have generated the following data: Table 1 shows that the highest rank is 26- 33 years old. In Table 2 Gender, the highest rank is male. Table 3 Job Description: The highest rank is staff, which got 73.33%. Table 4 How the respondents assess the employee in terms of assisting customers: the highest weighted mean is 3.27. Table 5, in terms of Reports, the highest weighted mean is 2.93. Table 6 shows that in terms of work, the highest weighted mean is 3. Table 7: Is there any significant relationship between the office environment and employee productivity shows that the highest weighted is 3.47. Table 8 What are the problems encountered in the office environment to the productivity of the employee in ambiance? Shows the highest weighted mean is 4.13. Table 9 Temperature: the highest weighted mean is 2.53. In Table 10, equipment, the highest weighted is 3.06. The development of the impact of the office environment on the productivity of matarik construction supply allows us to have an idea about the environment of construction supply. It also helps to identify the problems, and using this information, wise decisions can be made to tackle the issue appropriately. The study used a quantitative research design as best suited for investigation and to achieve the purpose of the study. Data were collected by distributing questionnaires to the 15 employees at Matarik Construction Supply. The result of the study revealed that, to some extent, The result demonstrates the need for the employees and staff to develop and organize the office environment to have a good and conducive work environment.